The Classification and Prediction of Ferroptosis-Related Genes in ALS: A Pilot Study - Zhang, Qianqian; Zhao, Huihui; Luo, Maotao; Cheng, Xi; Li, Yanan; Li, Qingyang; Wang, Zheng; Niu, Qi (Frontiers in Genetics, 2022)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease characterized by progressive muscle paralysis, which followed by the degeneration of motor neurons in the motor cortex of brainstem and spinal cord. The etiology of sporadic ALS (sALS) is still unknown, limiting the exploration of potentially treatments. Ferroptosis is a new form of cell death and reported closely associated with Alzheimer disease (AD), Parkinson disease (PD), and ALS. In this study, we used datasets (autopsy data and blood data) from Gene Expression Omnibus (GEO) to explore the role of Ferroptosis and ferroptosis-related genes (FRGs) alterations in ALS. Gene set enrichment analysis (GESA) found that the activated ferroptosis pathway displayed a higher enrichment score and the expression of 26 ferroptosis genes showed obvious group differences between ALS and controls. Using Weighted gene correlation network analysis (WGCNA), we identified FRGs associated with ALS, of which the Gene Ontology (GO) analysis displayed that biological process of oxidative stress was the most to be involved in. KEGG pathway analysis revealed that the FRGs were enriched not only in ferroptosis pathways, but also in autophagy, FoxO and mTOR signaling pathways. 21 FRGs ( NR4A1, CYBB, DRD4, SETD1B, LAMP2, ACSL4, MYB, PROM2 , CHMP5, ULK1, AKR1C2, TGFBR1, TMBIM4, MLLT1, PSAT1, HIF1A, LINC00336, AMN , SLC38A1, CISD1, and GABARAPL2) in the autopsy data and 16 FRGs ( NR4A1, DRD4, SETD1B, MYB, PROM2, CHMP5, ULK1, AKR1C2, TGFBR1, TMBIM4, MLLT1, HIF1A, LINC00336, IL33, SLC38A1 ,and CISD1 ) in the blood data were identified as target genes by least absolute shrinkage and selection operator analysis (LASSO), which gene signature could differentiate ALS patients from controls. Finally, the higher expression of CHMP5 and SLC38A1 in whole blood, the shorter lifespan of ALS patients. In summary, our study presents potential biomarkers for the diagnosis and prognosis of ALS.